Cambios detectados en la capa mucinosa en el ojo seco evaporativo, después del tratamiento con dos sustitutos lagrimales.
The tear film, a complex structure, thin and delicate structure; plays a crucial role in ensuring the health and well-being of the eyes, since helps provide nutrients, maintain hydration, offer protection against microorganisms and eliminate unwanted particles from the ocular surface.